Preparation method of gelidium nanocellulose-based antifouling paint
Cellulose is extracted by eutectic solvents in the stone cauliflower residue, and combined with enzymatic decomposition and oxidation treatment, the stone cauliflower nanocellulose-based anti-fouling coating was prepared, which solved the toxicity and environmental pollution problems of traditional anti-fouling coatings, and achieved non-toxicity. Efficient bio-anti-fouling coating with excellent self-cleaning and anti-fouling effects.
Patent Information
- Application Number
- CN202411421175.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing antifouling coatings have toxicity and environmental pollution problems, and traditional cellulose extraction methods have negative impacts on the environment and product quality.
Cellulose is extracted by eutectic solvent in the slag of slag, combined with cellulase enzymatic lysis and TEMPO oxidation method to prepare slagli nanocellulose, and polymerized with octamine and dopamine hydrochloride by one pot method, and finally EGCG is added To improve anti-fouling performance.
It realizes non-toxic and efficient biological antifouling coatings, simplifies the preparation process, reduces production costs, and has excellent self-cleaning and antifouling effects. It is suitable for hull antifouling coatings.
Smart Images

Figure CN119432169A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing a Gelidium nanocellulose-based antifouling coating. Background Art
[0002] Agar is also known as sea jelly, chicken foot vegetable, horse hair, dog hair vegetable and phoenix tail. It belongs to the Agaraceae family, Eurythophyta class, Rhodophyta order. At present, the main use of Agar is to produce agar. The processing waste after agar extraction has not received widespread attention, which has had a huge impact on resource waste and environmental pollution.
[0003] Cellulose is an important natural polysaccharide that is widely present in plant cell walls and is the main component of renewable resources. However, traditional cellulose extraction methods often use large amounts of organic solvents and high-energy consumption processes, which not only pollute the environment but may also have a negative impact on the quality of the extracted cellulose. Therefore, the development of green and efficient cellulose extraction technology is of great scientific and economic significance.
[0004] With the rapid development of the marine industry, the impact of marine fouling on the shipping industry and the marine environment has also attracted more and more attention. When biofouling occurs on the surface of the hull, it will cause a lot of serious harm. For example, bacteria, fungi and algae in the ocean can form biofilms on the surface of metal, wood or polymers within 48 hours, causing the hull to become rough, increase weight, increase navigation resistance, reduce speed and fuel efficiency, increase fuel consumption by 40%, and increase navigation costs by 77%. In addition, biofouling increases the frequency of ship maintenance, causes waste of resources, and produces toxic waste, seriously polluting the environment. At the same time, it will also cause the performance of the coating to deteriorate, accelerate hull corrosion, shorten the service life of equipment, and may cause biological invasion. Due to the economic losses and ecological hazards caused by marine biofouling, people have long begun to explore ways to prevent biofouling. Among them, antifouling coatings are considered to be an effective and economical solution. Antifouling coatings can reduce the attachment of oil and biofilms, thereby reducing fuel consumption and the frequency of ship maintenance. In addition, it can also delay hull corrosion, protect the metal matrix, and significantly reduce the maintenance costs of ships. Since the 1970s, organotin (TBT) has been widely used in antifouling paints, but it interferes with the endocrine system of mollusks, leading to population degradation and reduction in number, seriously affecting the marine ecology and potentially endangering human safety. The International Maritime Organization (IMO) banned the use of organotin antifouling paints in 2008. Since then, copper-rich antifouling paints have become alternatives, but the accumulation of copper has led to the reappearance of marine pollution and food chain enrichment problems, and the use of copper-containing substances has gradually been restricted. Therefore, the development of non-toxic and efficient biological antifouling coatings has become a research hotspot for new antifouling materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a Gelidium nanocellulose-based antifouling coating.
[0007] The technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing a Gelidium nanocellulose-based antifouling coating, comprising the following steps:
[0009] S1, mixing choline chloride-carboxylic acid deep eutectic solvent with agar-agar residue and heating in an oil bath to obtain agar-agar cellulose;
[0010] S2, treating the agar cellulose with cellulase enzymatic hydrolysis and TEMPO oxidation in sequence to obtain agar nanocellulose;
[0011] S3, placing the agar-agar nanocellulose and octadecylamine in a certain mass ratio in an ethanol aqueous solution and ultrasonically dissolving them, then adding a certain mass of dopamine hydrochloride, adjusting the pH value, and performing heating reaction polymerization at a certain temperature and time by a "one-pot method" to obtain agar-agar nanocellulose-based super-hydrophobic coating;
[0012] S4. Finally, a certain amount of EGCG is added and stirred evenly to obtain a Gelidium nanocellulose-based antifouling coating.
[0013] The invention proposes a method for preparing a gelatin nanocellulose-based antifouling coating. For the waste generated during the processing of gelatin, cellulose is first extracted from the gelatin residue by a low eutectic solvent. Compared with the traditional chemical extraction method, it not only has the advantages of high cellulose extraction rate and short extraction time, but also avoids the large-scale use of organic solvents, which is green and environmentally friendly. Then, the gelatin nanocellulose is further modified by a method of cellulase enzymolysis combined with TEMPO oxidation, which significantly improves the yield and oxidation efficiency of gelatin nanocellulose, and is more conducive to its application in the field of coatings. Subsequently, the gelatin nanocellulose is polymerized with octadecylamine and dopamine hydrochloride by a "one-pot method". The long-chain structure of octadecylamine and the excellent adhesion of dopamine are used to give the gelatin nanocellulose-based coating super-hydrophobic properties. This method simplifies the preparation process, shortens the time, and improves the production efficiency. Finally, by adding EGCG, the coating is further given excellent self-cleaning effect and antifouling effect. The invention not only provides an effective method for the reuse of gelatin waste, but also develops a new type of bio-based antifouling coating through green chemical technology, which contributes to the sustainable development of related industrial fields.
[0014] Preferably, in step S1, the mass ratio of the deep eutectic solvent to the agar-agar residue is 20:1;
[0015] The conditions of the oil bath heating are: reaction temperature is 100°C, reaction time is 3h;
[0016] The low eutectic solvent is prepared by mixing the choline chloride as a hydrogen bond acceptor with four carboxylic acids, namely acetic acid, lactic acid, oxalic acid and formic acid, as hydrogen bond donors in a certain molar ratio under anhydrous conditions, heating at 60° C. for 2 hours, and then screening by examining the effect on the cellulose content of agar.
[0017] More preferably, the low eutectic solvent is prepared by mixing the choline chloride and the lactic acid in a molar ratio of 1:2 under anhydrous conditions and heating at 60° C. for 2 h.
[0018] Preferably, in step S2, the conditions of the enzymatic hydrolysis treatment are: enzyme substrate ratio is 10% w / w, enzymatic hydrolysis pH is 4.8, enzymatic hydrolysis temperature is 60° C., and enzymatic hydrolysis time is 3 h.
[0019] Preferably, in step S2, the TEMPO oxidation method specifically comprises the following steps: placing 1 g of agar-agar cellulose nanofibrils obtained by enzymatic hydrolysis of the cellulase in an anhydrous sodium carbonate / sodium bicarbonate buffer solution, adding 0.017 g of TEMPO and 0.115 g of sodium bromide, stirring until fully dissolved, then adding a certain specific volume of sodium hypochlorite, adjusting the system to a certain pH value with sodium hydroxide solution and glacial acetic acid solution, and performing an oxidation reaction for a certain period of time;
[0020] Among them, the specific volume of sodium hypochlorite, the pH value of the oxidation system and the oxidation reaction time were optimized through single factor experiments with the yield and potential of agar-agar nanocellulose as indicators.
[0021] More preferably, the optimal process conditions of the TEMPO oxidation method are: the specific volume of the sodium hypochlorite is 11 mL / g, the pH value of the oxidation system is 10.5, and the oxidation reaction time is 24 h.
[0022] Preferably, in step S3, the mass ratio of agar-agar nanocellulose to octadecylamine, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride, the polymerization reaction temperature and the polymerization reaction time are obtained by single factor experiment optimization with the contact angle of the coating as an indicator.
[0023] More preferably, the optimal process conditions of the one-pot method are: the mass ratio of the agar nanocellulose to octadecylamine is 1:2, the mass ratio of the agar nanocellulose to dopamine hydrochloride is 1:2, the polymerization reaction temperature is 50° C., and the polymerization reaction time is 16 h.
[0024] Preferably, in step S4, the amount of EGCG added is screened by examining the effect on the contact angle and antibacterial activity of the coating.
[0025] More preferably, the mass proportion of the EGCG is 2% of the mass of the agar-agar nanocellulose-based super-hydrophobic coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the preparation method of the agar-agar nanocellulose-based antifouling coating of Example 1;
[0027] Figure 2 The effect of different oxidation parameters on the yield and potential of agar-agar nanocellulose in Example 1, A is the oxidation reaction time, B is the pH value of the oxidation system, C is the specific volume of sodium hypochlorite, and different letters indicate significant differences (p<0.05);
[0028] Figure 3 The influence of different process parameters on the contact angle of the coating in Example 1, A is the mass ratio of agar-agar nanocellulose (TOCN) to octadecylamine (ODA), B is the mass ratio of agar-agar nanocellulose to dopamine hydrochloride (PDA), C is the polymerization temperature, D is the polymerization time, and different letters indicate significant differences (p<0.05);
[0029] Figure 4 The effect of different EGCG addition amounts on the contact angle of the coating in Example 1, different letters indicate significant differences (p<0.05);
[0030] Figure 5 Comparison photos of the colony counts of bacteria adhered to the surface of samples with different EGCG addition amounts after dilution culture in Example 1;
[0031] Figure 6 Schematic diagram of the self-cleaning process of sand and chalk dust with different coatings, A is ODA@TOCN@PDA, B is ODA@TOCN@PDA@EGCG;
[0032] Figure 7 The chemical stability test results of different coatings, A is the salt ion concentration test, where a is immersion in 1.5wt% NaCl solution, b is immersion in 3.5wt% NaCl solution, and c is immersion in 5.5wt% NaCl solution; B is the acid and alkali resistance test, where d is immersion in strong acid, e is immersion in neutral, and f is immersion in strong alkali;
[0033] Figure 8 The universality test results of different coating substrates, a is a blank substrate, b is a substrate coated with ODA@TOCN@PDA, and c is a substrate coated with ODA@TOCN@PDA@EGCG;
[0034] Fig. 9The adhesion morphologies of contaminants with different coatings, a is the morphology of the blank iron sheet, b is the morphology of the sheet coated with ODA@TOCN@PDA, and c is the morphology of the sheet coated with ODA@TOCN@PDA@EGCG. DETAILED DESCRIPTION
[0035] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.
[0036] Determination method:
[0037] 1. Cellulose content of agar: determined by the nitric acid-ethanol method.
[0038] 2. Potential of agar-agar nanocellulose: Agar-agar nanocellulose was prepared into a 0.06% (w / v) suspension using ultrapure water, subjected to ultrasonic treatment for 10 min, and measured using Zeta potential and nanoparticle size analyzer analysis.
[0039] 3. Contact angle of the coating: The coating was applied to a base material (metal sheet), dried in an oven for 10 hours, and measured using a dynamic contact angle tester.
[0040] 4. Antibacterial activity of coatings: Leucobacter chromiireducens was used as the experimental strain, and the plate colony counting method was used to calculate the antibacterial rate of different coating samples. All samples must be sterilized with high-temperature steam before testing, and then different samples are immersed in bacterial suspension (10 5 cell / mL) and cultured at 28°C for 24h. Subsequently, the bacteria adhering to the surface of the sample were washed into 5mL of LB broth medium. The LB broth medium containing the washed bacteria was then appropriately diluted, and 30μL of the diluted bacterial solution was inoculated on the solid culture medium. After culturing at 28°C for 36h, the number of colonies on the culture medium was counted and compared with the untreated sample to calculate the antibacterial rate.
[0041] The embodiment of the present invention provides a method for preparing a Gelidium nanocellulose-based antifouling coating, comprising the following steps:
[0042] S1, mixing choline chloride-carboxylic acid deep eutectic solvent with agar-agar residue and heating in an oil bath to obtain agar-agar cellulose;
[0043] S2, treating the agar cellulose with cellulase enzymatic hydrolysis and TEMPO oxidation in sequence to obtain agar nanocellulose;
[0044] S3, placing agar-agar nanocellulose and octadecylamine in a certain mass ratio in an ethanol aqueous solution and ultrasonically dissolving them, then adding a certain mass of dopamine hydrochloride, adjusting the pH value, and performing a heating reaction polymerization at a certain temperature and time by a "one-pot method" to obtain agar-agar nanocellulose-based super-hydrophobic coating;
[0045] S4. Finally, a certain amount of EGCG is added and stirred evenly to obtain a Gelidium nanocellulose-based antifouling coating.
[0046] In the present invention, in step S1, after the oil bath heating, the following steps are further included: centrifugation to remove the supernatant, washing with deionized water for several times to remove the residual solvent, and drying at 90°C.
[0047] In step S2, after the enzymatic hydrolysis treatment, the following steps are also included: centrifugation, washing with deionized water several times, collecting the precipitate, ultrasonic crushing treatment, and freeze-drying, wherein the conditions of the ultrasonic crushing treatment are: ultrasonic power of 150W, working time of 2s, pause time of 3s, and ultrasonic time of 10min.
[0048] The TEMPO oxidation treatment further includes the following steps: adding ethanol, dialysis to neutrality, and freeze drying.
[0049] In step S3, after the heating reaction polymerization, the following steps are further included: centrifugation at 8000 rpm for 20 minutes, washing with deionized water and anhydrous ethanol for several times, and collecting the precipitate. In addition, the concentration of the ethanol aqueous solution used in this step is 50%, and the conditions for ultrasonic dissolution are: ultrasonic power of 350 W, ultrasonic frequency of 28 KHz, ultrasonic temperature of 30-50° C., and ultrasonic time of 30 minutes.
[0050] In step S4, before adding EGCG, the following steps are also included: adding anhydrous ethanol to the agar-agar nanocellulose-based super-hydrophobic coating and uniformly dispersing it by ultrasonication.
[0051] In a preferred embodiment of the present invention, in step S1, the mass ratio of the deep eutectic solvent to the agar-agar residue is 20:1;
[0052] The conditions for oil bath heating were: reaction temperature 100°C, reaction time 3 h;
[0053] The low eutectic solvent is prepared by mixing choline chloride as a hydrogen bond acceptor with four carboxylic acids, namely acetic acid, lactic acid, oxalic acid and formic acid, as hydrogen bond donors in a certain molar ratio under anhydrous conditions and heating at 60°C for 2 hours. It is then screened by examining its effect on the cellulose content of agar.
[0054] In a more preferred embodiment of the present invention, the low eutectic solvent is prepared by mixing choline chloride and lactic acid in a molar ratio of 1:2 under anhydrous conditions and heating at 60° C. for 2 h.
[0055] In a preferred embodiment of the present invention, in step S2, the conditions for enzymatic treatment are: enzyme substrate ratio is 10% w / w, enzymatic pH is 4.8, enzymatic temperature is 60° C., and enzymatic time is 3 h.
[0056] In a preferred embodiment of the present invention, in step S2, the TEMPO oxidation method specifically comprises the following steps: placing 1 g of agar-agar cellulose nanofibrils obtained by enzymatic hydrolysis of cellulose in an anhydrous sodium carbonate / sodium bicarbonate buffer solution, adding 0.017 g of TEMPO and 0.115 g of sodium bromide, stirring until fully dissolved, then adding a certain specific volume of sodium hypochlorite, adjusting the system to a certain pH value with sodium hydroxide solution and glacial acetic acid solution, and performing an oxidation reaction for a certain period of time;
[0057] Among them, the specific volume of sodium hypochlorite, the pH value of the oxidation system and the oxidation reaction time were optimized through single factor experiments with the yield and potential of agar-agar nanocellulose as indicators.
[0058] In the present invention, the ratio of the amount of the buffer solution to the agar cellulose nanofibrils is 100:1 mL / g, the mass ratio of anhydrous sodium carbonate to sodium bicarbonate in the buffer solution is 2:1, and the pH value of the solution is 10.
[0059] In a more preferred embodiment of the present invention, the optimal process conditions of the TEMPO oxidation method are: the specific volume of sodium hypochlorite is 11 mL / g, the pH value of the oxidation system is 10.5, and the oxidation reaction time is 24 h.
[0060] In a preferred embodiment of the present invention, in step S3, the mass ratio of agar-agar nanocellulose to octadecylamine, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride, the polymerization reaction temperature and the polymerization reaction time are obtained by single factor experimental optimization using the contact angle of the coating as an indicator.
[0061] In a more preferred embodiment of the present invention, the optimal process conditions of the one-pot method are: the mass ratio of agar-agar nanocellulose to octadecylamine is 1:2, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride is 1:2, the polymerization reaction temperature is 50°C, and the polymerization reaction time is 16h.
[0062] In a preferred embodiment of the present invention, in step S4, the amount of EGCG added is screened by examining the effect on the contact angle and antibacterial activity of the coating.
[0063] In a more preferred embodiment of the present invention, the mass proportion of EGCG is 2% of the mass of the agar-agar nanocellulose-based super-hydrophobic coating.
[0064] The technical solution of the present invention is further described and illustrated below based on specific embodiments.
[0065] Example 1
[0066] Reference Figure 1 , a method for preparing a Gelidium nanocellulose-based antifouling coating, comprising the following steps:
[0067] S1. The choline chloride-carboxylic acid low eutectic solvent and the agar-agar residue were mixed in a mass ratio of 20:1, and then heated in an oil bath. The mixture was reacted at 100° C. for 3 h. After the reaction was completed, the supernatant was removed by centrifugation, and the mixture was washed with deionized water for 3 times to remove the residual solvent. The mixture was dried at 90° C. to obtain agar-agar cellulose.
[0068] Among them, the low eutectic solvent is prepared by mixing choline chloride as a hydrogen bond acceptor with four carboxylic acids, acetic acid, lactic acid, oxalic acid and formic acid, as hydrogen bond donors in a molar ratio of 1:2, 1:2, 1:1, and 1:2 under anhydrous conditions and heating at 60°C for 2h. The cellulose of agar was prepared according to the method of step S1 above, and the cellulose was obtained by examining its effect on the cellulose content of agar. The results are recorded in Table 1.
[0069] Table 1 Cellulose content of Gelidium agar residue treated with different types of deep eutectic solvents
[0070]
[0071] As shown in Table 1, the cellulose content extracted by heating the low eutectic solvent composed of choline chloride-lactic acid with agar-agar residue oil bath is the highest. Therefore, the low eutectic solvent prepared by mixing choline chloride and lactic acid in a molar ratio of 1:2 under anhydrous conditions and heating at 60°C for 2h was selected as the best low eutectic solvent for subsequent experiments.
[0072] S2, treating the agar-agar cellulose with cellulase enzymatic hydrolysis and TEMPO oxidation in sequence to obtain agar-agar nanocellulose.
[0073] Among them, the cellulase enzymatic hydrolysis treatment specifically includes the following steps: dispersing the agar cellulose into ultrapure water through ultrasonic treatment, and after being evenly dispersed, adding cellulase into the system at an enzyme-substrate ratio of 10% w / w, adjusting the pH of the system to 4.8, and performing enzymatic hydrolysis at 60°C for 3 hours. After the enzymatic hydrolysis is completed, centrifuging, washing with deionized water for 3 times, collecting the precipitate, and performing ultrasonic crushing treatment with an ultrasonic power of 150W, with a working time of 2s, a pause time of 3s, an ultrasonic time of 10min, and freeze-drying to obtain agar cellulose nanofibrils.
[0074] The TEMPO oxidation treatment specifically includes the following steps: placing 1 g of agar cellulose nanofibrils obtained by enzymatic hydrolysis of cellulase in 100 mL of anhydrous sodium carbonate / sodium bicarbonate buffer solution (the mass ratio of anhydrous sodium carbonate to sodium bicarbonate is 2:1, and the solution pH is 10), adding 0.017 g of TEMPO and 0.115 g of sodium bromide, stirring until fully dissolved, then adding a certain volume of sodium hypochlorite, adjusting the system to a certain pH value with sodium hydroxide solution and glacial acetic acid solution, carrying out an oxidation reaction for a certain period of time, and at the end of the reaction, adding 5 mL of ethanol to terminate the reaction, dialyzing to neutrality, and freeze-drying;
[0075] Among them, the specific volume of sodium hypochlorite, the pH value of the oxidation system and the oxidation reaction time were optimized through single factor experiments with the yield and potential of agar-agar nanocellulose as indicators.
[0076] The screening step of the oxidation reaction time includes: under the conditions of a fixed specific volume of sodium hypochlorite of 11 mL / g and a pH value of the oxidation system of 10.5, adjusting the oxidation reaction time to 18 h, 20 h, 22 h, 24 h, and 26 h, respectively, preparing agar-agar nanocellulose according to the method of step S2 above, and determining the yield and potential of agar-agar nanocellulose. The results are recorded in Figure 2 A.
[0077] like Figure 2 As shown in A, the best effect of oxidation reaction time on the yield and potential of agar-agar nanocellulose is 24 h.
[0078] The step of screening the pH value of the oxidation system includes: under the conditions of a fixed specific volume of sodium hypochlorite of 11 mL / g and an oxidation reaction time of 24 h, adjusting the pH value of the oxidation system to 9, 9.5, 10, 10.5, and 11, respectively, preparing agar-agar nanocellulose according to the method of step S2 above, and determining the yield and potential of agar-agar nanocellulose. The results are recorded in Figure 2 B.
[0079] like Figure 2 As shown in B, the pH value of the oxidation system has the best effect on the yield and potential of agar-agar nanocellulose, with 10.5 being the best.
[0080] The screening step of the specific volume of sodium hypochlorite includes: under the condition that the pH value of the oxidation system is fixed at 10.5 and the oxidation reaction time is 24h, the specific volume of sodium hypochlorite is adjusted to 7mL / g, 9mL / g, 11mL / g, 13mL / g, and 15mL / g respectively, and agar-agar nanocellulose is prepared according to the method of step S2 above, and the yield and potential of agar-agar nanocellulose are determined. The results are recorded in Figure 2 C.
[0081] like Figure 2As shown in C, the effect of sodium hypochlorite volume ratio on the yield and potential of agar-agar nanocellulose is best at 11 mL / g.
[0082] Therefore, the present invention analyzes the influence of various parameters on the yield and potential of agar-agar nanocellulose through single-factor experiments, selects the specific volume of sodium hypochlorite as 11 mL / g, the pH value of the oxidation system as 10.5, and the oxidation reaction time as 24 h as the optimal process conditions for TEMPO oxidation method, and conducts subsequent experiments.
[0083] S3. Place agar-agar nanocellulose and octadecylamine in a certain mass ratio in a 50% ethanol aqueous solution and ultrasonically dissolve them. The ultrasonic power is 350 W, the ultrasonic frequency is 28 kHz, the ultrasonic temperature is 30°C, and the ultrasonic time is 30 min. Then, a certain mass of dopamine hydrochloride is added, and the pH value is adjusted to 8.5. The polymerization is carried out by heating reaction at a certain temperature and time through a "one-pot method". The mixture is centrifuged at 8000 rpm for 20 min, washed 3 times with deionized water and anhydrous ethanol, and the precipitate is collected to obtain agar-agar nanocellulose-based super hydrophobic coating.
[0084] Among them, the mass ratio of agar-agar nanocellulose to octadecylamine, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride, the polymerization reaction temperature and the polymerization reaction time were optimized through single factor experiments with the contact angle of the coating as an indicator.
[0085] The screening step of the mass ratio of agar-agar nanocellulose to octadecylamine includes: under the conditions of fixing the mass ratio of agar-agar nanocellulose to dopamine hydrochloride to 1:2, the polymerization reaction temperature to 50°C, and the polymerization reaction time to 16h, respectively adjusting the mass ratio of agar-agar nanocellulose to octadecylamine to 1:0.5, 1:1, 1:1.5, 1:2, and 1:2.5, preparing agar-agar nanocellulose-based super-hydrophobic coating according to the method of step S3 above, and measuring the contact angle of the coating. The results are recorded in Figure 3 A.
[0086] like Figure 3 As shown in A, the mass ratio of agar-agar nanocellulose to octadecylamine on the hydrophobic effect of agar-agar nanocellulose-based coating is best at 1:2.
[0087] The screening step of the mass ratio of agar-agar nanocellulose to dopamine hydrochloride includes: under the conditions of fixing the mass ratio of agar-agar nanocellulose to octadecylamine at 1:2, the polymerization reaction temperature at 50°C, and the polymerization reaction time at 16h, respectively adjusting the mass ratio of agar-agar nanocellulose to dopamine hydrochloride to 1:0.5, 1:1, 1:1.5, 1:2, and 1:2.5, preparing agar-agar nanocellulose-based super-hydrophobic coating according to the method of step S3 above, and measuring the contact angle of the coating. The results are recorded in Figure 3 B.
[0088] like Figure 3 As shown in B, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride on the hydrophobic effect of agar-agar nanocellulose-based coating is best at 1:2.
[0089] The step of screening the polymerization reaction temperature includes: under the conditions that the mass ratio of agar-agar nanocellulose to octadecylamine is fixed at 1:2, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride is 1:2, and the polymerization reaction time is 16h, respectively adjusting the polymerization reaction temperature to 30°C, 40°C, 50°C, 60°C, and 70°C, preparing agar-agar nanocellulose-based super-hydrophobic coating according to the method of step S3 above, and measuring the contact angle of the coating. The results are recorded in Figure 3 C.
[0090] like Figure 3 As shown in Figure C, the best polymerization temperature for the hydrophobic effect of agar-agar nanocellulose-based coatings is 50°C.
[0091] The step of screening the polymerization reaction time includes: under the conditions of fixing the mass ratio of agar-agar nanocellulose to octadecylamine at 1:2, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride at 1:2, and the polymerization reaction temperature at 50°C, respectively adjusting the polymerization reaction time to 10h, 12h, 14h, 16h, and 18h, preparing the agar-agar nanocellulose-based super-hydrophobic coating according to the method of step S3 above, and measuring the contact angle of the coating. The results are recorded in Figure 3 D.
[0092] like Figure 3 As shown in D, the best polymerization time for the hydrophobic effect of agar-agar nanocellulose-based coatings is 16 h.
[0093] Therefore, the present invention analyzes the influence of various parameters on the contact angle of the coating through a single factor experiment, selects a mass ratio of agar-agar nanocellulose to octadecylamine of 1:2, a mass ratio of agar-agar nanocellulose to dopamine hydrochloride of 1:2, a polymerization reaction temperature of 50°C, and a polymerization reaction time of 16 h as the optimal process conditions for the one-pot method, and conducts subsequent experiments.
[0094] S4. Anhydrous ethanol is added to the agar-agar nanocellulose-based super-hydrophobic coating, and ultrasonic dispersion is performed uniformly. Finally, a certain amount of EGCG is added and stirred uniformly to obtain the agar-agar nanocellulose-based antifouling coating.
[0095] The amount of EGCG added was prepared according to the method of step S4 above, and the effect of EGCG on the contact angle and antibacterial activity of the coating was screened by examining the effect of 0%, 1%, 2%, 4%, and 8% of the mass of the agar-agar nanocellulose-based super-hydrophobic coating. The results are recorded in Tables 2 and Figure 4-5 .
[0096] Table 2 Colony count and antibacterial rate of samples with different EGCG addition amounts
[0097]
[0098] from Figure 4 It can be seen that the optimal range of EGCG addition on the hydrophobic effect of agar-agar nanocellulose-based coatings is 1-4%. Figure 5 It can be seen that the optimal range of EGCG addition on the antibacterial effect of agar-agar nanocellulose-based coatings is 2-8%. Overall, 2% of EGCG is the best.
[0099] Application performance testing
[0100] (1) Self-cleaning performance
[0101] The agar nanocellulose-based antifouling coating (denoted as ODA@TOCN@PDA@EGCG) prepared under the optimal process conditions in Example 1 and the agar nanocellulose-based superhydrophobic coating (denoted as ODA@TOCN@PDA) prepared without adding EGCG were drop-coated on an iron sheet with a thickness of 0.6 mm × a width of 2.5 cm × a length of 8 cm to check its self-cleaning performance, and sand and chalk dust were used to simulate pollutants. The iron sheet coated with the antifouling coating was tilted in a culture dish and covered with sand and chalk dust in a random pattern. The sand and chalk dust on the iron sheet were rinsed with a syringe, and the process of pollutants on the sample surface being washed away by water droplets was recorded by taking pictures.
[0102] The results are as follows Figure 6 As shown, water can easily roll off the glass surface with sand and chalk dust, and sand and chalk dust will roll off the glass surface, indicating that the synthesized coating has significant self-cleaning properties.
[0103] (2) Chemical stability
[0104] ODA@TOCN@PDA@EGCG and ODA@TOCN@PDA prepared under the optimal process conditions in Example 1 were tested in terms of acid and alkali resistance and salt ion resistance.
[0105] Salt ion resistance: The coated iron sheet was immersed in 1.5%, 3.5%, and 5.5% NaCl solutions. After 3 days, the iron sheet was taken out, washed with distilled water and dried (about 3 minutes), and then the contact angle of a 3 μL water droplet on the surface was recorded.
[0106] The results are as follows Figure 7 As shown in A, the water contact angle of the coating hardly changed after the coating was immersed in solutions with different NaCl concentrations for 3 days, and the coating maintained good non-wetting properties.
[0107] Acid and alkali resistance: The coated iron sheet was immersed in solutions of pH = 1, pH = 7 and pH = 13. After 3 days, the iron sheet was taken out, washed with distilled water and dried (about 3 minutes), and then the contact angle of a 3 μL water drop on the surface was recorded.
[0108] The results are as follows Figure 7 As shown in B, the results show that after immersion in strong acid, neutral and strong alkaline solutions for 3 days, the water contact angle of the coating has almost no change, and the coating maintains good non-wetting properties.
[0109] (3) Universality
[0110] The ODA@TOCN@PDA@EGCG and ODA@TOCN@PDA prepared under the optimal process conditions in Example 1 were drop-coated on five different substrates, including glass, iron sheet, A4 paper, cotton, and filter paper, and dried in an oven for 10 hours. 5 μL of four different liquids, including Sprite, milk, coffee, and barley tea, were dropped and recorded by taking photos.
[0111] The results are as follows Figure 8 As shown, the coatings on different substrates maintain good liquid-repellent properties for different liquids.
[0112] (4) Antifouling effect
[0113] The antifouling effect of ODA@TOCN@PDA@EGCG and ODA@TOCN@PDA prepared under the optimal process conditions in Example 1 was evaluated by indoor hanging board experiment. The seawater used in this experiment was taken from Changle District, Fuzhou City, Fujian Province. The coating was applied on an iron sheet with a thickness of 0.6mm × width of 2.5cm × 8cm. Before immersion in seawater, it was marked prominently to record the original state. Natural seawater was added to the transparent pool. The coated sample was placed vertically in the glass pool and allowed to soak. After one month, photos were taken to record the changes on the coating surface.
[0114] The results are as follows Fig. 9 As shown, after one month, the blank iron sheet was covered with rust and had a lot of stains on the surface, the coating surface coated with the paint without adding ECGG had a lot of stains, and the coating surface coated with the agar nanocellulose-based antifouling paint of the present invention had less stains.
[0115] In summary, the present invention has the following advantages:
[0116] (1) The deep dissolved solvent (DES) method was used to extract agar cellulose. This method significantly reduced the impact on the environment, avoided the pollution problems that may be caused by traditional chemical solvents, and embodied the concept of green chemistry.
[0117] (2) By using the enzymatic hydrolysis-TEMPO oxidation combined technology and precisely controlling the specific volume of sodium hypochlorite, the pH value of the oxidation system, and the oxidation reaction time, the extracted agar cellulose can be efficiently converted into agar nanocellulose with nanoscale size and more active groups, opening up new possibilities for the industrial application of cellulose-based coatings.
[0118] (3) A one-pot process was adopted to successfully prepare a super-hydrophobic coating with a surface microstructure by precisely controlling the polymerization ratio of nanocellulose to octadecylamine and dopamine hydrochloride, and optimizing the temperature and time of the polymerization reaction. The super-hydrophobic coating can effectively repel water and dirt and achieve a self-cleaning effect, thereby reducing the cleaning frequency and maintenance costs, bringing convenience to users.
[0119] (4) The natural antifouling agent EGCG is innovatively introduced. It is derived from plants and is environmentally friendly. The final coating not only has super-hydrophobic properties, but also can effectively prevent the adhesion of dirt, grease and microorganisms, has self-cleaning properties, and has good acid, alkali and salt ion resistance. In the indoor hanging board experiment, the agar-agar nanocellulose-based antifouling coating of the present invention exhibits excellent antifouling effect.
[0120] The agar-agar nanocellulose-based antifouling coating of the present invention not only exhibits the advantages of high efficiency and environmental protection in the preparation process, but also achieves excellent super-hydrophobic, self-cleaning, acid and alkali resistance, salt resistance and other antifouling effects in performance. These characteristics make the present invention have broad application prospects in the field of environmentally friendly materials and provide strong technical support for achieving green chemistry and sustainable development goals.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a Gelidium nanocellulose-based antifouling coating, comprising the following steps: S1, mixing choline chloride-carboxylic acid deep eutectic solvent with agar-agar residue and heating in an oil bath to obtain agar-agar cellulose; S2, treating the agar cellulose with cellulase enzymatic hydrolysis and TEMPO oxidation in sequence to obtain agar nanocellulose; S3, placing the agar-agar nanocellulose and octadecylamine in a certain mass ratio in an ethanol aqueous solution and ultrasonically dissolving them, then adding a certain mass of dopamine hydrochloride, adjusting the pH value, and performing heating reaction polymerization at a certain temperature and time by a "one-pot method" to obtain agar-agar nanocellulose-based super-hydrophobic coating; S4. Finally, a certain amount of EGCG is added and stirred evenly to obtain a Gelidium nanocellulose-based antifouling coating.
2. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 1, characterized in that: In step S1, the mass ratio of the deep eutectic solvent to the agar-agar residue is 20:1; The conditions of the oil bath heating are: reaction temperature is 100°C, reaction time is 3h; The low eutectic solvent is prepared by mixing the choline chloride as a hydrogen bond acceptor with four carboxylic acids, namely acetic acid, lactic acid, oxalic acid and formic acid, as hydrogen bond donors in a certain molar ratio under anhydrous conditions, heating at 60° C. for 2 hours, and then screening by examining the effect on the cellulose content of agar.
3. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 2, characterized in that: The low eutectic solvent is prepared by mixing the choline chloride and the lactic acid in a molar ratio of 1:2 under anhydrous conditions and heating at 60° C. for 2 hours.
4. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 1, characterized in that: In step S2, the conditions of the enzymatic hydrolysis treatment are: enzyme substrate ratio is 10% w / w, enzymatic hydrolysis pH is 4.8, enzymatic hydrolysis temperature is 60° C., and enzymatic hydrolysis time is 3 h.
5. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 1 or 4, characterized in that: In step S2, the TEMPO oxidation method specifically includes the following steps: placing 1 g of agar-agar cellulose nanofibrils obtained by enzymatic hydrolysis of the cellulase in an anhydrous sodium carbonate / sodium bicarbonate buffer solution, adding 0.017 g of TEMPO and 0.115 g of sodium bromide, stirring until fully dissolved, then adding a certain specific volume of sodium hypochlorite, adjusting the system to a certain pH value with sodium hydroxide solution and glacial acetic acid solution, and performing an oxidation reaction for a certain period of time; Among them, the specific volume of sodium hypochlorite, the pH value of the oxidation system and the oxidation reaction time were optimized through single factor experiments with the yield and potential of agar-agar nanocellulose as indicators.
6. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 5, characterized in that: The optimal process conditions of the TEMPO oxidation method are: the specific volume of the sodium hypochlorite is 11 mL / g, the pH value of the oxidation system is 10.5, and the oxidation reaction time is 24 h.
7. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 1, characterized in that: In step S3, the mass ratio of agar-agar nanocellulose to octadecylamine, the mass ratio of agar-agar nanocellulose to dopamine hydrochloride, the polymerization reaction temperature and the polymerization reaction time are obtained by single factor experiment optimization with the contact angle of the coating as an index.
8. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 7, characterized in that: The optimal process conditions of the one-pot method are: the mass ratio of the agar nanocellulose to octadecylamine is 1:2, the mass ratio of the agar nanocellulose to dopamine hydrochloride is 1:2, the polymerization reaction temperature is 50° C., and the polymerization reaction time is 16 h.
9. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 1, characterized in that: In step S4, the amount of EGCG added is screened by examining the effect on the contact angle and antibacterial activity of the coating.
10. The method for preparing the agar-agar nanocellulose-based antifouling coating according to claim 9, characterized in that: The mass proportion of the EGCG is 2% of the mass of the agar-agar nanocellulose-based super-hydrophobic coating.
Citation Information
Patent Citations
Super-hydrophobic modification method of nanocellulose
CN113773404A
Method for preparing pennisetum napier nanocellulose by using eutectic solvent in combination with ultrasound
CN115418876A
Method for extracting dark tea polysaccharide by ultrasonic-assisted deep-eutectic solvent
CN115611991A